No Effect of the Right Posterior Parietal Cortex tDCS in Dual-Target Visual Search - Lanina, Alyona A.; Feurra, Matteo; Gorbunova, Elena S. (Frontiers in Psychology, 2018)
«Subsequent search misses» represent a decrease in accuracy at detecting a second target in a visual search task. In this study, we tested the possibility to modulate this effect via inhibition of the right posterior parietal cortex trough transcranial direct current stimulation (tDCS). The target stimuli were T-shapes presented among L-shaped distractors. The participant’s task was to detect targets or to report their absence. For each trial, targets could be represented by one high-salient target, one low-salient target, two different targets (one high salient and one low salient), two high salient targets, two low salient targets, or no targets at all (catch-trials). Offline tDCS was applied over the right (target site) or left (control site) posterior parietal cortex. Sham stimulation over the right posterior parietal cortex was included as a control (placebo). Stimulation lasted for 10 minutes. Afterwards, participants were asked to perform the experiment. Our findings suggest that stimulation did not modulate any of the task conditions, suggesting potential limitation of the study: either tDCS was not enough powerful to modulate the task performance or the task was too easy to be modulated by stimulation.